Análisis no lineal de la estructura del Hospital Darío Machuca Palacios del cantón La Troncal en Ecuador - Guaraca, Francisco Xavier Calle; Guevara, Bernardo Andrés Feijoo; Calero, M.Sc, Ing. José Fernando Vásquez (KnE Engineering, 2018)
The hospital "Darío Machuca Palacios" is located in La Troncal (Cañar-Ecuador). In the nonlinear dynamic analysis of this hospital was determined inconsistencies in its design, such as non-compliance with maximum permissible drifts established by the Ecuadorian Construction Standard (NEC, as per its Spanish acronym), demonstrating vulnerability and possible collapse of the hospital. Considering that it is an essential building according to the NEC of seismic danger, it needs to be maintained in correct post-earthquake operation. For this reason the behavior of the structure with seismic isolation systems at their base was simulated, offering results that analyzed in depth could determine that this measure of seismic protection is adequate. Keywords: nonlinear dynamic analysis, essential building, seismic isolation systems.